Genetic characterization of horse breeds (Equus caballus) of Western India - PATEL, ASHISH C; PARIKH, R C; MACWAN, SHEFALI; TANK, P H; MARADIA, M G; RANK, D N (The Indian Journal of Animal Sciences, 2020)
Assessment of genetic diversity and population structure of population through molecular markers allows determining their extinction risk and to manage and conserve the respective population. The present study was undertaken for population genetic analysis at a molecular level of horse breeds for planning conservation, utilization and improvement in the livelihood. Gujarat has three recognized horse breeds Kathiawari, Marwari and Kachchhi- Sindhi. The genetic characterization and differentiation analysis among and within these breeds was analyzed using 26 microsatellite markers out of which 25 markers were polymorphic while one was monomorphic. The present study indicated that Marwari and Kathiawari horse breeds are genetically nearer as compared to Kathiawari— Kachchhi-Sindhi and Marwari—Kachchhi-Sindhi. The observed number of alleles in all three breeds ranged from 2 (NVHEQ21) to 16 (ASB17). The within population in breeding estimate (FIS) was less than zero, indicating absence of inbreeding in Kathiawari, Marwari and Kachchhi-Sindhi breed. The Wilcox text, sign test and standardized difference test in present study revealed the presence of significant heterozygotic excess in both IAM and SMM model demonstrating that these three breeds of horse has showed recent genetic bottleneck.